(untitled) (Proceedings of International Educators Conference, 2024)
This article reaches inside the intricate portrayal of detective figures in Agatha Christie’s "The ABC Murders," highlighting the evolution of the detective genre through a psychological lens. By analyzing Hercule Poirot alongside the murderer, the article argues that Christie transcends traditional narrative structures, offering a nuanced exploration of human motivations and morality. The work emphasizes the complexity of both the detective’s character and the criminal’s psyche, illustrating how these elements reflect broader societal issues. The discussion also addresses common misconceptions about detective fiction, advocating for a deeper appreciation of its social commentary and psychological depth. Ultimately, this analysis positions "The ABC Murders" as a pivotal work that continues to resonate with contemporary readers interested in character-driven narratives.